THE MYTH OF MATERIAL SUCCESS AS REFLECTED IN SAM WALTON: MADE IN AMERICA-MY STORY - Utut Kurniati (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
American myth of material success had been orchestrated five basic beliefs that were reflected in Sam Walton’s biography, Sam Walton: Made in America-My Story. Those beliefs were: 1) Having a strong will to be successful man in America, Sam Walton was aware that the American democracy allowed its citizens to rise above any limitation in which they may have been born; 2) Then, he rose up from his limitation by hard work. His hard work successfully brought him to the riches and physical comforts; 3) He believed that those rewards came to those who were deserving of them (virtuous); 4) He also believed that those rewards came to those who had the drive and ambition to attain them. Therefore, he was optimistic to attain success in America; 5) Hard work to attain success made Sam Walton a lucky man who received good luck in his life. As a result, his dream of being a successful man in America came true.Keywords: the myth of material success, American dream, hard work